Improved bone metabolism in female elite athletes after vitamin K supplementation - Craciun, A. M.; Wolf, J.; Knapen, M. H.; Brouns, F.; Vermeer, C. (International Journal of Sports Medicine, 1998)
In female elite athletes strenuous exercise may result in hypoestrogenism and amenorrhoea. As a consequence a low peak bone mass and rapid bone loss are often seen in relatively young athletes. In postmenopausal women, increased intake of vitamin K may result in an increase of serum markers for bone formation, a decrease of urinary markers for bone resorption, and a decrease in urinary calcium loss. In the present paper we report an intervention study among eight female athletes, four of whom had been amenorrhoeic for more than one year, whereas the others had been using oral contraceptives. All participants received vitamin K supplementation (10 mg/day) during one month, and various bone markers were measured before and after treatment. At baseline the athletes not using oral contraceptives were biochemically vitamin K-deficient as deduced from the calcium binding capacity of the circulating bone protein osteocalcin. In all subjects increased vitamin K was associated with an increased calcium-binding capacity of osteocalcin. In the low-estrogen group vitamin K supplementation induced a 15-20% increase of bone formation markers and a parallel 20-25% decrease of bone resorption markers. This shift is suggestive for an improved balance between bone formation and resorption.